The Advances and Challenges in Enzymatic C-glycosylation of Flavonoids in Plants - Gao, Hui-Yao; Liu, Yan; Tan, Fei-Fan; Zhu, Li-Wen; Jia, Kai-Zhi; Tang, Ya-Jie (Current Pharmaceutical Design, 2022)
Flavonoid glycosides play determinant roles in plants and have considerable potential for applications in medicine and biotechnology. Glycosyltransferases transfer a sugar moiety from uridine diphosphateactivated sugar molecules to an acceptor flavonoid via C-O and C-C linkages. Compared with O-glycosyl flavonoids, C-glycosyl flavonoids are more stable, resistant to glycosidase or acid hydrolysis, exhibit better pharmacological properties, and have received more attention. In this study, we discuss the mining of C-glycosyl flavones and the corresponding C-glycosyltransferases and evaluate the differences in structure and catalytic mechanisms between C-glycosyltransferase and O-glycosyltransferase. We conclude that promiscuity and specificity are key determinants for general flavonoid C-glycosyltransferase engineering and summarize the C-glycosyltransferase engineering strategy. A thorough understanding of the properties, catalytic mechanisms, and engineering of C-glycosyltransferases will be critical for future biotechnological applications in areas such as the production of desired C-glycosyl flavonoids for nutritional or medicinal use.
Keywords: specificity engineering